2022
DOI: 10.1016/j.snb.2021.131152
|View full text |Cite
|
Sign up to set email alerts
|

3-Dimensional electrical impedance spectroscopy for in situ endoluminal mapping of metabolically active plaques

Abstract: Electrical impedance spectroscopy (EIS) has been recognized to characterize oxidized low-density lipoprotein (oxLDL) in the metabolically active plaque. However, intravascular deployment of 3-D EIS-derived electrical impedance tomography (EIT) for endoluminal mapping of oxLDL-laden arterial walls remains an unmet clinical challenge. To this end, we designed the 6-point microelectrode arrays that were circumferentially configurated onto the balloon catheter for 15 intravascular EIS permutations. In parallel, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Materials used in our EIS catheter, such as PtB, gold, polyimide (PI), and silicone, have all been found by previous studies to be safe for in vivo applications 20–23 . No adverse responses were observed in this study, and to the best of our knowledge, no immunogenic responses were reported in prior literature that tested similarly constructed EIS devices in vivo on animal models 24–27 . Despite the promising outlook of the materials implemented in our catheter, approval by the Food and Drug Administration (FDA) is still required to proceed with Phase I clinical study of our device 28 …”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Materials used in our EIS catheter, such as PtB, gold, polyimide (PI), and silicone, have all been found by previous studies to be safe for in vivo applications 20–23 . No adverse responses were observed in this study, and to the best of our knowledge, no immunogenic responses were reported in prior literature that tested similarly constructed EIS devices in vivo on animal models 24–27 . Despite the promising outlook of the materials implemented in our catheter, approval by the Food and Drug Administration (FDA) is still required to proceed with Phase I clinical study of our device 28 …”
Section: Resultsmentioning
confidence: 86%
“…Lastly, we were able to show similarities in impedimetric properties between the atherosclerotic components of pigs and that of ex vivo human arteries, whereas previous studies have largely been limited to animal models. [24][25][26][27] Thus, our study adds to the translational potential of intravascular EIS, paving the way towards its clinical application to predict plaque rupture in patients, in real time.…”
Section: Metrics To Evaluate Model Performancementioning
confidence: 90%
See 2 more Smart Citations
“…Advances in vascular catheter-based deployment allow for implantation of biomedical devices such as arterial stents and bioprosthetic valves. Through a percutaneous incision to the femoral or radial arteries, catheter-based deployment obviates the need for thoracotomy for cardiac bypass surgery or valve replacement (30)(31)(32) and shortens recovery times and hospital stay (33)(34)(35)(36). Recently, artificial stent and electric blood vessels enable a small and implantable endovascular device for targeted control for localized therapy (37,38).…”
Section: Introductionmentioning
confidence: 99%